Maritime Security in the Border Area of Indonesia-Philippines: Study in the Waters of Sangihe Islands Regency and Talaud Island Regency - Niode, Burhan; Rachman, Ismail; Waworundeng, Welly (International Journal of Asian Social Science, 2021)
This study aimed to identify various activities in the waters of Sangihe Islands Regency and Talaud Islands Regency that could threaten the maritime security of both regencies. The research was located in several areas: Sangihe Islands Regency, Talaud Islands Regency, and several cities in North Sulawesi Province (Manado City and Bitung City). Data and information were collected through an in-depth interview and literature review. The data obtained was then analyzed using qualitative method. The result shows that the potential maritime threats in the waters of Sangihe Islands Regency and Talaud Islands Regency involve activities such as: (1) illegal entry and illegal trade, carried out by residents living in the border areas of Indonesia (Sangihe Islands Regency and Talaud Islands Regency) and residents living in the southern Philippines region, (2) illegal fishing, starting from fish theft conducted by foreign fisheries, illicit fish trade by local fisheries to foreign vessels at sea, to fish bombing and alcohol smuggling by local fisheries, and (3) the route of terrorist activity. This route demonstrates how terrorist groups carry out their activities by utilizing the Indonesia-Philippines border area as a route for their mobility to enter and exit, as well as for the circulation of weapons for terrorist activities in Eastern Indonesia.